KP Fry Enterprise / Aiman Hafiz Zahari... [et al.] - Zahari, Aiman Hafiz; Hamzah, Siti Nadia; Rahim Shah, Bibi Nur Syamierah; Amir Haszuwanni, Mohd Aidilfarez (2020)
We are making a product which is called Korean spicy chicken. We are producing spicy fried chicken with variety in the level of spiciness which is mild, medium and hot. Our product is targeted towards the food enthusiast all over the country. The price that we charge for our product is RM 10 per unit. This price is pretty low compared to our competitors' product. This is because most of the restaurant that sell similar product focus on a fine dining experience, while our shop is focused on the fast food style. Our company is located at 152, Jalan Dato Bandar Tunggal ,Bandar Seremban, 70000 Seremban, Negeri Sembilan. Our competitors are Nanda and Dubuyo. Our competitors have the following strength which is being well known among the foodies and their shop are made to look like a real Korean restaurant. This made the people feels like they are in Korea whenever they eat there because of the scenery of the shop itself. However, they have their on weakness, which is being being a bit expensive. We intend to introduce our product through the product attributes, trade name, brand name, packaging, labeling and warranty and also after sale service. Second, price strategy are based on cost and based on what price that the competitors put. Besides that, we also use promotion strategy such as banner and signboard. Other than that, we also use electronic media to spread the information about our product. For example, Instagram, Facebook, Twitter and Whatsapp. Furthermore, we also do offline marketing strategy. We will spread out at a few area to gives out flyers about our product. We also rely on word-of-mouth marketing.